Talent Management Development on Government Institutions Regional Civil Service Agency Semarang - Meida Rachmawati; Mohamad Rahimi Mohamad Rosman; Mohd Zafian Bin Mohd Zawawi; Mokhammad Khukaim Barkhowa; Joko Pramono (CV. Publikasi Indonesia, 2023)
The organization's talent needs for the next five years are a translation of the strategy, and a reflection of the organization's vision and mission, taking into account internal demands as well as external demands. Quality aspects included in determining talent needs include knowledge and skills obtained from experience, competence, and personality in terms of organizational culture, it is clearly stated that institutional capacity development has indicators in institutionalizing a productive and positive organizational work culture based on the noble values of the nation's culture. According to the results of research at the Regional Civil Service Agency, Semarang Regency has implemented a value system that is the basis of ethics at work. It can be in the form of politeness, hospitality, communication that shows a noble value of the nation. Thus, from participatory and democratic comes the existence of work motivation that is always growing. By strengthening the value of employee discipline, the development of institutional capacity at the Semarang Regency Regional Civil Service Agency is maximized, this is strengthened by the enactment of PP No. 53 of 2010 concerning Employee Discipline, so that supervision is stricter and punishment is more firm and severe. In the institutional capacity building program at the Regional Civil Service Agency of Semarang Regency, a budget allocation is needed to support the implementation of all organizational activities. In accordance with World Bank theory which emphasizes the attention of talent management to the focus of the organizational environment which leads to financial and budgetary support in realizing all activities and needs of the organization. This type of research is Descriptive research. The approach used is a qualitative approach and a conceptual approach. The data source used is secondary data. Data analysis was carried out in a qualitative descriptive manner. Drawing conclusions is carried out by the deductive method, which is to draw conclusions from general to specific, especially those related to the research topic, namely the development of management talent towards government institutions. Capacity building takes a long time and requires long-term commitment and all parties involved. In the development of talent management of an organization both public and private sectors, Collective Commitments are the basic capital that must be continuously developed and maintained properly. This talent management commitment is not only for power holders, but covers all components in the organization. The influence of mutual commitment is very large, because this factor is the basis of the entire design of activities and goals to be achieved together. It is expected to strengthen and strengthen the budget allocation method in accordance with the vision, mission and objectives of governance as well as the development of regional revenue sources.